Impact of Undetected Comorbidity on Treatment and Outcomes of Breast Cancer - Robert I. Griffiths; Michelle L. Gleeson; José M. Valderas; Mark D. Danese (International Journal of Breast Cancer)
Preexisting comorbidity adversely impacts breast cancer treatment and outcomes. We examined the incremental impact of comorbidity undetected until cancer. We followed breast cancer patients in SEER-Medicare from 12 months before to 84 months after diagnosis. Two comorbidity indices were constructed: the National Cancer Institute index, using 12 months of claims before cancer, and a second index for previously undetected conditions, using three months after cancer. Conditions present in the first were excluded from the second. Overall, 6,184 (10.1%) had ≥1 undetected comorbidity. Chronic obstructive pulmonary disease (38%) was the most common undetected condition. In multivariable analyses that adjusted for comorbidity detected before cancer, older age, later stage, higher grade, and poor performance status all were associated with higher odds of ≥1 undetected comorbidity. In stage I–III cancer, undetected comorbidity was associated with lower adjusted odds of receiving adjuvant chemotherapy (Odds Ratio (OR) = 0.81, 95% Confidence Interval (CI) 0.73–0.90, P<0.0001; OR=0.38, 95% CI 0.30–0.49, P<0.0001; index score 1 or ≥2, respectively), and with increased mortality (Hazard Ratio (HR) = 1.45, 95% CI 1.38–1.53, P<0.0001; HR=2.38, 95% CI 2.18–2.60, P<0.0001; index score 1 or ≥2). Undetected comorbidity is associated with less aggressive treatment and higher mortality in breast cancer.